2018
DOI: 10.1002/zaac.201800088
|View full text |Cite
|
Sign up to set email alerts
|

DNA Groove‐binding Ability of Luminescent Platinum(II) Complexes based on a Family of Tridentate N^N^C Ligands Bearing Differently Substituted Alkyl Tethers

Abstract: A family of luminescent PtII complexes is presented capable of binding DNA duplexes via groove binding. The complexes are based on a tridentate ligand with N^N^C donor functionality bearing a triazole, a pyridine and a phenyl entity. The triazole group is used to attach a series of pendant dodecane tethers with differently charged functional head groups (neutral hydroxyl group, anionic sulfate group, cationic tetraalkylammonium group). The DNA‐binding behavior of the three resulting PtII complexes was characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In contrast in the case of L , only concurrent enhancement in the absorption intensity (i. e. hyperchromism) was detected without hypochromism and any significant shift in the wavelength at 274 nm . Since there is any amendment in the position of absorption bands (red or blue shift), it can be concluded that ligand L interacts through groove binding interactions with CT DNA …”
Section: Dna Binding Studiesmentioning
confidence: 85%
“…In contrast in the case of L , only concurrent enhancement in the absorption intensity (i. e. hyperchromism) was detected without hypochromism and any significant shift in the wavelength at 274 nm . Since there is any amendment in the position of absorption bands (red or blue shift), it can be concluded that ligand L interacts through groove binding interactions with CT DNA …”
Section: Dna Binding Studiesmentioning
confidence: 85%
“…Most of the luminescent platinum­(II) complexes are based on terpyridyl ligands and their derivatives, a platinum porphyrin complex, complexes with pincer ligands, such as N^C^N-, N^N^C-, N^N^N-coordinating ligands, and some cyclometalated platinum derivatives . The origin of the intense color and luminescence of these complexes is often from metal-to-ligand charge transfer (d → π*) .…”
Section: Introductionmentioning
confidence: 99%
“…8−10 The potential and real application of platinum(II) complexes involves organic light-emitting diodes, 11−15 biolabeling, cytotoxicity, phototoxicity, and their ability to bind nucleic acids and proteins. 16 Most of the luminescent platinum(II) complexes are based on terpyridyl ligands 17 and their derivatives, a platinum porphyrin complex, 18 complexes with pincer ligands, such as N^C^N-, 19 N^N^C-, 20 N^N^N-coordinating ligands, 11 and some cyclometalated platinum derivatives. 14 The origin of the intense color and luminescence of these complexes is often from metal-to-ligand charge transfer (d → π*).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In general, the lifetimes are reminiscent of what had been reported previously for a related Pt(II) complex interacting non-covalently with ctDNA via groove-binding. 40 …”
Section: Resultsmentioning
confidence: 99%
“…In general, the lifetimes are reminiscent of what had been reported previously for a related Pt(II) complex interacting non-covalently with ctDNA via groovebinding. 40 Interestingly, duplex V and single-stranded oligonucleotide ODN3 respond differently to the presence of dissolved molecular dioxygen. The luminescence intensity of the excimers above 600 nm is much less sensitive to dissolved dioxygen than that of the monomers at 500 nm.…”
Section: Time-resolved Photoluminescence Spectroscopymentioning
confidence: 99%